Penerapan Algoritma K-Means Pada Penjualan Saldo Transportasi Online Studi Kasus Konter XYZ - Hilman Mutaqin (Jurnal Algoritma, 2023)
The XYZ counter is a counter in Tasikmalaya with one of the products it sells, online transportation balances such as Maxim, Gojek, and Grab. With the increasing number of online drivers, more and more transactions take place so that more and more data is generated. However, this data is not processed so that it accumulates and does not provide new knowledge for the counter owner. The purpose of this research is to cluster sales of online transportation balances so that they become input, especially the XYZ counter promotion strategy. The method used is clustering with the K-Means algorithm to produce clusters based on the nominal purchase price. The dataset used in this study amounted to 4,867 data but after cleansing it became 2,642 data. The dataset was obtained from XYZ counter sales in October 2022. This study produced 2 clusters with cluster C1, namely a low nominal of 2,499 data with a percentage of 94.59%, while the number of clusters C2 with a high nominal value of 143 data with a percentage of 5.41 . The results of this study indicate that the k-means algorithm can be used for clustering sales of online transportation balances at the XYZ counter, and sales of online transportation balances are quite good because the number of data clusters with low nominal is more than clusters with high nominal.